Low-power cooling codes with efficient encoding and decoding - Chee, Yeow Meng (2020)
A class of low-power cooling (LPC) codes, to control simultaneously both the peak temperature and the average power consumption of interconnects, were introduced recently. An (n, t, w)-LPC code is a coding scheme over n wires that (A) avoids state transitions on the t hottest wires (cooling), and (B) limit the number of transitions to w in each transmission (low-power). A few constructions for large LPC codes that have efficient encoding and decoding schemes, are given. In particular, when w is fixed, we construct LPC codes of size (n/w) w-1 and show that these LPC codes can be modified to correct errors efficiently. We further present a construction for large LPC codes based on a mapping from cooling codes to LPC codes.